Effectiveness of the breaststroke leg movement in relation to selected time-space, anthropometric, flexibility, and force data - Vervaecke, H. U. B.; Persyn, U. J. J. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
Most practitioners believe that a good breaststroke kick ensures good propulsion in the total competitive stroke as well as in lifesaving. Velocity fluctuation curves of a breaststroke cycle of some top swimmers (Persyn, 1974; Persyn, De Maeyer, and Vervaecke, 1975) show that the most important acceleration occurs during the kick. The action of the arms that follows keeps the velocity constant or causes a slight acceleration. Within this kick, the greatest acceleration occurs during leg extension. Because the path described by the feet in relation to the water is directed partly backward, we deduced that a paddle wheel propulsion principle was being used. Also during the squeezing action of the legs, in which there is no backward displacement of the feet, acceleration continues. This can be explained only on the basis of a propeller propulsion principle. Among the best swimmers, the ability to perform these propulsion techniques apparently results from a particular flexibility of the ankles and from some anthropometric characteristics of the feet, e.g., shape and surface. Therefore, in this stroke, in which the velocity fluctuates strongly, the kick is important to acceleration of the body and thus to the performance of champion swimmers.